2021
DOI: 10.1029/2020jg005828
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Factors of Methane in Tropical Lakes of Different Depths

Abstract: Methane (CH 4 ) is a more potent greenhouse gas in terms of climate forcing than carbon dioxide (CO 2 ) (Forster et al., 2007;IPCC, 2018), and in the recent decades, natural sources of CH 4 have accounted for about 22%-30% of mean global CH 4 emissions (Saunois et al., 2020). Although existing estimates and models are updated periodically, our confidence in these remains low because of limited observational data. The importance of global CH 4 models that are based on well-represented estimates from different l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Although MOBs are commonly present through the whole water column (Lew and Glinska-Lewczuk, 2018), they have low methane oxidation activity in surface waters due to the inhibitory effect of strong light (Dumestre et al, 1999;Murase et al, 2005). In deeper small maar lakes (i.e., the SMLs), since the near bottom layer is euxinic (Mendoza et al, 2021), it can retard methane oxidation by aerobic MOB, such as Type I and II (Rahalkar et al, 2009;Schubert et al, 2010), suggesting that their optimal growth condition may exist in the mid-depth suboxic layer, from which we did not collect any POM samples. A reason why the dominant group and vertical pattern of the MOB in our study were inconsistent with those of other lakes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although MOBs are commonly present through the whole water column (Lew and Glinska-Lewczuk, 2018), they have low methane oxidation activity in surface waters due to the inhibitory effect of strong light (Dumestre et al, 1999;Murase et al, 2005). In deeper small maar lakes (i.e., the SMLs), since the near bottom layer is euxinic (Mendoza et al, 2021), it can retard methane oxidation by aerobic MOB, such as Type I and II (Rahalkar et al, 2009;Schubert et al, 2010), suggesting that their optimal growth condition may exist in the mid-depth suboxic layer, from which we did not collect any POM samples. A reason why the dominant group and vertical pattern of the MOB in our study were inconsistent with those of other lakes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the LLDA, a governmental agency for the environmental protection of Laguna Lake and its watershed, recently implemented an ordinance to reduce the total area of fish cages in the SMLs, some of the lakes are still regarded as eutrophic (Mendoza et al, 2019a). In addition, Mendoza-Pascual et al (2021) recently updated the trophic status of three of the study lakes based on total phosphorus concentrations and classified them as eutrophic to hypereutrophic lakes. In contrast, in the Lake Taal food web, the POM FA compositions were characterized by terrestrial plants (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Among the SML, these two lakes -dubbed as the "twin lakes" -were classified as oligotrophic lakes (Zapanta et al 2008). However, these were eventually reclassified into mesotrophic (Mendoza et al 2019) and eventually into eutrophic lakes based on more recent data (Mendoza-Pascual et al 2021), indicating that despite the efforts made to rehabilitate these "twin lakes," these are continuously suffering from declining water quality.…”
Section: Discussionmentioning
confidence: 99%
“…Laguna is home to seven neighboring lakes, known as the SML, which are used for both aquaculture and tourism (Brillo 2016a, b;Mendoza et al 2019). Various studies have shown the declining water quality of the lakes brought about by increased nutrient inputs through excess fish feeds and domestic runoffs (Brillo 2015(Brillo , 2016aBannister et al 2019;Mendoza et al 2019;Mendoza-Pascual et al 2021), transforming it into an environment ideal for the propagation of A. dorsalis. Papa et al (2012) reported that A. dorsalis was the only calanoid species in the SML.…”
Section: Introductionmentioning
confidence: 99%
“…Latitudinal differences in climatic conditions lead to distinctive seasonality in mixing, stratification and phytoplankton succession in tropical lakes (Cordero & Baldia, 2015), which may have distinctive vertical (water column) structures that are susceptible to seasonal variations (Kraemer et al, 2015;Lau et al, 2020;Mesman et al, 2021). However, the magnitude of seasonal temperature changes is smaller than at higher latitudes, meaning that some tropical lakes never completely mix (Boehrer & Schultze, 2008;Bannister et al, 2019), whilst in others, seasonal mixing may occur as a disturbance effect of monsoonal airflows or cyclones (Klug et al, 2012;Mendoza-Pascual et al, 2021). Lakes at low latitudes are also potentially more sensitive to changes in temperature and nutrient availability than their cooler climate equivalents (Lewis, 1987;Adrian et al, 2009), whilst nitrogen (N) may be more limiting, and nutrient cycling more efficient (Abell et al, 2012;Bannister et al, 2019).…”
Section: Introductionmentioning
confidence: 99%